Mild to moderate post-COVID-19 alters markers of lymphocyte activation, exhaustion, and immunometabolic responses that can be partially associated by physical activity level— an observational sub-analysis fit- COVID study - Silva, Bruna Spolador de Alencar; Pereira, Telmo; Minuzzi, Luciele Guerra; Padilha, Camila Souza; Figueiredo, Caique; Olean-Oliveira, Tiago; dos Santos, Ivete Vera Medeiros; von Ah Morano, Ana Elisa; Marchioto Júnior, Osmar; Ribeiro, José Procópio Jabur; Dos Santos, Vanessa Ribeiro; Seelaender, Marília; et al. (Frontiers in Immunology, 2023)
Aim This study aimed to evaluate if physical activity is associated with systemic and cellular immunometabolic responses, in young adults after mild-to-moderate COVID-19 infection. Methods Mild- to- moderate post-COVID-19 patients (70.50 ± 43.10 days of diagnosis; age: 29.4 (21.9– 34.9) years; BMI: 25.5 ± 4.3 kg m2 n = 20) and healthy age-matched controls (age: 29.3 (21.2 – 32.6) years; BMI: 25.4 ± 4.7 kg m2; n = 20) were evaluated. Physical activity levels (PAL), body composition, dietary habits, muscular and pulmonary function, mental health, sleep quality, metabolic parameters, immune phenotypic characterization, stimulated whole blood and PBMC culture (cytokine production), mRNA, and mitochondrial respiration in PBMCs were evaluated. Results The post-COVID-19 group exhibited lower levels of moderate to vigorous physical activity (MVPA) (p = 0.038); therefore, all study comparisons were performed with adjustment for MVPA. Post-COVID-19 impacted the pulmonary function (FEV1, FEV1%pred, FVC, and FVC %pred) compared with the control (p adjusted by MVPA (p adj) <0.05). Post-COVID-19 exhibited lower levels of serum IL-6 (p adj <0.01), whereas it showed higher serum IL-10, triglyceride, leptin, IgG, ACE activity, TNFRSF1A, and PGE2 (p adj <0.05) levels compared with controls. Post-COVID-19 presented a lower percentage of Treg cells (p adj = 0.03) and altered markers of lymphocyte activation and exhaustion (lower CD28 expression in CD8+ T cells (p adj = 0.014), whereas CD4+T cells showed higher PD1 expression (p adj = 0.037)) compared with the control group. Finally, post- COVID-19 presented an increased LPS-stimulated whole- blood IL-10 concentration (p adj <0.01). When exploring mitochondrial respiration and gene expression in PBMCs, we observed a higher LEAK state value (p adj <0.01), lower OXPHOS activity (complex I) (p adj = 0.04), and expression of the Rev-Erb-α clock mRNA after LPS stimulation in the post-COVID-19 patients than in the control (p adj <0.01). Mainly, PAL was associated with changes in IL-10, triglyceride, and leptin levels in the plasma of post-COVID-19 patients. PAL was also associated with modulation of the peripheral frequency of Treg cells and the expression of PD-1 in CD8+ T cells, although it abrogated the statistical effect in the analysis of TNF-α and IL-6 production by LPS- and PMA-stimulated PBMC of post-COVID-19 patients. Conclusion Young adults after mild-to-moderate SARS-CoV-2 infection appeared to have lower physical activity levels, which can be associated with clinical and immunometabolic responses in a complex manner.